Virtualization Analisis Kinerja CPU dan RAM pada VirtualBox untuk Validasi Lingkungan IaaS Lokal - Restu Prayoga, Hendrika; Latifah, Noor (Jurnal Sistem Informasi Galuh, 2026)
In cloud computing, the Infrastructure as a Service (IaaS) model relies heavily on virtualization technology. Developers commonly use Type-2 hypervisors as local testing environments before deploying systems to the actual cloud, with Oracle VM VirtualBox being one of the most widely used platforms. However, the additional virtualization layer can introduce performance overhead on critical resources such as CPU and RAM, potentially affecting the validity of test results. This study aims to measure the percentage of CPU and RAM performance overhead caused by VirtualBox. A comparative quantitative experiment was conducted by evaluating the performance of the Host Operating System (OS) as the baseline and the Guest OS running on VirtualBox using specialized benchmarking tools. The findings indicate increased RAM latency and reduced CPU performance. These results assist developers in optimizing resource allocation and provide essential empirical data to evaluate the feasibility of using VirtualBox as a tool for performance validation in IaaS environments. Additionally, this study highlights how variations in VirtualBox configurations—such as the number of virtual cores and the amount of allocated RAM—affect the magnitude of overhead. This demonstrates that improper configuration choices can lead to significant performance deviations when compared to physical system conditions.